Modern Analyses of Macroeconomic Indices for Medium and Long Term Plans in Georgia - Giorkhelidze, Demur (European Scientific Journal, ESJ, 2024)
This paper analyzes the economic growth of Georgia through the lens of two key indicators: income/GDP per worker (representing productivity) and income/GDP per capita (representing prosperity). It emphasizes the importance of using Purchasing Power Parity (PPP) adjusted data to avoid misleading comparisons between countries with different price levels. The paper highlights three key stylized facts about Georgia’s economy: Transformational Shock: Georgia’s GDP per capita fell dramatically by 468% in less than ten years due to the collapse of the Soviet economic system. This is a unique event in modern economic history, with no other country experiencing such a sharp decline; Unstable Growth Rates: Unlike the U.S. which shows a relatively stable 2% annual growth rate over 150 years, Georgia’s economic growth rates lack a clear trend and fluctuate significantly; Negative Correlation Between Cyclical Unemployment and GDP Gap: The cyclical unemployment rate and the GDP gap in Georgia are inversely correlated. As the unemployment rate falls below the natural rate of unemployment, the GDP gap widens, indicating potential overheating in the economy. The paper argues that existing models of economic growth, often based on developed economies with different macroeconomic realities, may not be suitable for analyzing Georgia’s situation. It calls for the development of models that explicitly consider the unique features of Georgia’s economy, including the transformational shock, unstable growth rates, and the relationship between unemployment and GDP. Overall, the paper raises important questions about the nature of economic growth in Georgia and the need for tailored models to understand its specific dynamics.